Comparison of the accuracy and completeness of records of serious vascular events in routinely collected data vs clinical trial–adjudicated direct follow-up data in the UK: secondary analysis of the ascend randomized clinical trial - Harper, C; Mafham, M; Herrington, W; Staplin, N; Stevens, W; Wallendszus, K; Haynes, R; Landray, MJ; Parish, S; Bowman, L; Armitage, J (American Medical Association, 2021)
Importance Routinely collected data could substantially decrease the cost of conducting trials.